Food security challenges in developing economies - Shamsudin, Mad Nasir (Faculty of Agriculture, Universiti Putra Malaysia, 2018)
The food sector in developing economies is facing challenging landscape in terms of supply and demand factors. Underinvestment in agriculture research, small scale farms with low level of technology, entrepreneurship, climate change, and depleting resources have affected food supply. In terms of demand, the trends in food consumption has been an increase in the consumption of a greater variety and volume of higher value and higher proteins foods (such as meat, fish and milk). This is at the expense of traditional sources of lower quality protein rather than the sources of traditional higher quality protein. The demand for staple food among the lower quintile of the population, however, still increased as the income elasticity of this group is high. Consumers also demand new food products, new packaging, more convenience, new delivery systems, and safer and more nutritious foods.